Based on Proteomics Data Revealing the Potential of Traditional Chinese Medicine in Treating Irritable Bowel Syndrome - Yizhan Wu; Fei Guo; Xiaoxia Xu; Ya Liu; Jiangwei Liu (Mediators of Inflammation, 2025)
Conclusion: These findings not only deepen our understanding of the pathophysiological mechanisms of IBS but also indicate potential molecular targets for the development of innovative treatment strategies while highlighting the broad application prospects of traditional Chinese medicine in the field of IBS treatment.